-19-1+26-37=-1-3m-8+4m

Simple and best practice solution for -19-1+26-37=-1-3m-8+4m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -19-1+26-37=-1-3m-8+4m equation:


Simplifying
-19 + -1 + 26 + -37 = -1 + -3m + -8 + 4m

Combine like terms: -19 + -1 = -20
-20 + 26 + -37 = -1 + -3m + -8 + 4m

Combine like terms: -20 + 26 = 6
6 + -37 = -1 + -3m + -8 + 4m

Combine like terms: 6 + -37 = -31
-31 = -1 + -3m + -8 + 4m

Reorder the terms:
-31 = -1 + -8 + -3m + 4m

Combine like terms: -1 + -8 = -9
-31 = -9 + -3m + 4m

Combine like terms: -3m + 4m = 1m
-31 = -9 + 1m

Solving
-31 = -9 + 1m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
-31 + -1m = -9 + 1m + -1m

Combine like terms: 1m + -1m = 0
-31 + -1m = -9 + 0
-31 + -1m = -9

Add '31' to each side of the equation.
-31 + 31 + -1m = -9 + 31

Combine like terms: -31 + 31 = 0
0 + -1m = -9 + 31
-1m = -9 + 31

Combine like terms: -9 + 31 = 22
-1m = 22

Divide each side by '-1'.
m = -22

Simplifying
m = -22

See similar equations:

| 8500=-200t^2+3600t | | 3*x+(-4)=6*x-4 | | 90=-2.5b | | 1.3+1.5=1.4 | | 4(2*x+2)=8*x+9 | | 6m-12n= | | .5x+8=1-.25x-7 | | Y=100x^2-81 | | 2a+-2=15.7 | | 55=0.2(55-10e) | | (10x-4)=12 | | 5z-14=8z+4 | | -n+7=n-9 | | x+x(2)+x+86=180 | | -2(6x-4)=8-12*x | | -6d=-8 | | 6-3x+2x^2-x^3=0 | | -x=7x+2 | | 4*x+19=-9-6x | | x+5=7x+2 | | 25-(-5)-7= | | 3x-22+65=180 | | 5=18a | | 3+x-4=7x-2 | | 2u^2+3u-20=0 | | 4*x+3=2(2x+9) | | (x-8)=x-3 | | 6+2(2-4x)=6x+2(2x-4) | | 30+40x=35 | | 55=285-10e | | 2(6x+10y)+8=0 | | 4(x-6)-10=2x |

Equations solver categories